KESESUAIAN WILAYAH PERLINDUNGAN TERUMBU KARANG PADA DESA – DESA PESISIR DI KECAMATAN NUSA PENIDA - I Dewa Gede Warmadewa; I Wayan Arthana; Ida Ayu Astarini (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2014)
Conserving natural resources are a necessity to ensure the sustainability of it is utilization. Throughthe determination of the suitability of the coastal villages on Nusa Penida as coral reef protected areas, it isexpected that all activities use of coastal resources will sustainable. The results showed Nusa Penida totalarea of coral reef ecosystems is 1.419 ha with fringing reef types. Based on live Nusa Penida’s coral reefcover conditions at a depth of 3 meters categorized as good condition (74%), for a depth of 10 meters theaverage condition of live coral cover categorized as good condition (64%). Depth of 10 meters showed interactionscoral communities are more stable than 3 meters. Suitability protected area of coral reefs was conducted in12 villages that have reef condition data at a depth of 10 meters. From 12 villages studied, 9 villages havesuitability as a protected area of coral reefs namely the Village of Pajukutan, Suana, Batu Nunggul, BatuMadeg, Sakti, Batu Kandik, Sekartaji, Toya Pakeh and Jungut Batu. From those villages, 4 villages have notake zone recomendation areas namely the Village of Jungut Batu, Toyapakeh, Batu Nunggul and Suana